Estimating water retention for major soils in the Hararghe region, Eastern Ethiopia - Tsehai, Kibeebw Kibret (University of the Free State, 2003)
Soil water retention IS a fundamental property controlling water storage and movement in the solurn. To determine the water retention characteristic curve is time consuming and expensive. Several attempts have been made to establish relationships between easily measurable soil properties, like particle size distribution, organic carbon content, and the water retention characteristic curve. Those relationships are referred to as pedotransfer functions (PTFs). More conveniently, it is described by analytical functions that are suitable in the solution of numerical flow equations as well as in implementation of closed-form methods for predicting other hydraulic properties, such as unsaturated hydraulic conductivity. The objectives of this study were to describe the water retention characteristics of soils from the Hararghe Region, eastern Ethiopia, in relation to certain soil properties; to identify water retention functions for describing the water retention characteristic curves of these soils and to develop a procedure for estimating water content either at certain matric potentials or the complete curve from readily available soil properties. Two approaches, point estimation and parametric estimation techniques, were used for estimating the water content at certain matric potentials and at any matric potential, respectively. To establish relationships between water retention and relevant soil properties, regression analyses were carried out. From the regression analyses, point PTFs that can be used to estimate the water content at certain matric potentials were developed. This was done firstly by using the complete data set consisting of 216 retention curves and secondly by dividing the complete data set into topsoil and subsoil samples. Due to observed differences in water retention characteristics, the subsoil samples were divided into two groups based on their silt (Si) to clay (C) ratio. The dividing line between these two groups was 0.75. The topsoil and the two subsoil groups were divided into classes based on their silt plus clay content. This resulted in 7 classes for topsoils and subsoils with Si:C ratios < 0.75 and 6 classes for the subsoils with Si:C ratios> 0.75. For all the point estimation PTFs, the silt plus clay content functions described the variability in water content best. The relationship between water content and silt plus clay content was curvilinear. In order to quantify the prediction accuracy of these equations, the mean of the mean absolute error (mMAE), the mean of the root mean square error (mRMSE), the mean of the mean bias error (mMBE), d-index of agreement and coefficient of determination (R2) were used. In some instances, the slopes and intercepts of the 1:1 lines, between measured and predicted values, were used. The silt plus clay content functions for the complete data set explained 78 to 87 % of the variability in water content at specific matric potentials. The mMBE ranged from -0.001 to -0.003 cm' cm", the mMAE 0.022 to 0.034 crrr' cm", the mRMSE 0.027 to 0.042 crrr' ern". The d-values ranged from 0.838 to 0.867. The silt plus clay content functions for the topsails explained 88 to 94 % of the variability in water retention with the mMBE ranging from 0 to -0.001 crrr' cm", mMAE 0.018 to 0.031 crrr' cm", mRMSE 0.024 to 0.036 cm3 ern" and the d-values 0.765 to 0.886. The silt plus clay content functions for the subsoils with Si:C ratios < 0.75 were able to explain 78 to 87 % of the variability in water retention with the mMBE ranging from -0.001 to -0.004 crrr' ern", mMAE 0.019 to 0.036 crrr' ern", mRMSE 0.023 to 0.045 cnr' cm" and d-values 0.793 to 0.884. The silt plus clay content function for the subsoils with Si:C ratios> 0.75 explained 86 to 98 % of the variability in water content with mMBE ranging from -0.001 to 0.004 cm' ern", mMAE 0.013 to 0.031 ern' cm", mRMSE 0.015 to 0.038 crrr' cm" and d-values 0.737 to 0.99l. Of the three groups, the mean values of the classes were used to develop PTFs with higher R2-values and lower errors compared with the PTFs developed from the complete data set in each respective group. From the six water retention functions tested, the Van Genuchten (1980) function, with the restriction m = 1 - lIn, gave the best description of the water retention curves, followed by the Smith (1992) and the ordinary power functions. Over all, the Brooks-Corey (1964) function gave the poorest description of the water retention curves studied. The parameters of the Smith (1992) and Hutson & Cass (1987) functions correlated better with relevant soil properties compared to the parameters of the Van Genuchten function. With the parametric approach the Smith (1992) function estimated water content for topsails and subsoils with Si:C ratios> 0.75 with a higher accuracy compared with the Van Genuchten and Hutson & Cass functions whereas the Hutson & Cass function was better for the subsoils with Si:C ratios < 0.75. Testing the functions derived from the point estimation and parameterization techniques on an independent data set indicated that both approaches estimated water content with a reasonable degree of accuracy, although the point estimation techniques gave slightly better results for the subsoils with Si:C ratios> 0.75.

Grondwaterretensie is 'n fundamentele eienskap wat die waterhouvermoë en - beweging in die solum beheer. Om die waterkarakteristiekekurwes van gronde te bepaal is 'n omslagtige en tydrowende proses. Verskeie pogings is aangewend om verwantskappe tussen maklik meetbare grondeienskappe, soos deeltjiegrootteverspreiding, koolstofinhoud en waterretensie af te lei. Hierdie verwantskappe word ook pedo-oordragfunksies genoem. Gerieflikheidshalwe moet hierdie funksie analities van aard wees sodat dit gebruik kan word om vloeivergelykings op te los en vir die voorspelling van hidrouliese eienskappe soos die onversadigde hidrouliese geleivermoë. Die doelwitte met hierdie ondersoek was i) om die waterretensie en verwante eienskappe van die gronde van die Hararge Streek in oostelike Ethiopië te bepaal; ii) om die funksie wat die waterretensiekurwes die beste pas te identifiseer en om iii) 'n prosedure te ontwikkel waarvolgens waterretensiekurwes, vanaf maklik bepaalbare grondeienskappe, voorspel kan word. Twee benaderings, nl. die punt- en parametriese beramingstegnieke is gebruik, waarvolgens die waterinhoud by spesifieke matrikspotensiale en die parameters van die waterretensiekurwe onderskeidelik beraam word. Die verwantskappe tussen waterrensie en die onderskeie grondeienskappe is by wyse van regressie-analieses bepaal. Punt pedo-oordragfunksies is oritwikkel waarmee die waterinhoude by spesifieke matrikspotensiaalwaardes vanaf die slik plus klei-inhoude van gronde beraam kan word. Eerstens is die volledige datastel, bestaande uit 216 retensiekurwes, en tweedens' groeperings van die data in bo- en ondergronde, gebruik vir die ontwikkeling van die funksies. Met die interpretasie van die ondergronddata is gevind dat dit in twee populasies, volgens die slik (S) tot klei (K) verhouding verdeel kan word. Die grens tussen die groepe was 0.75. Die groot hoeveelheid retensiekurwes binne elk van die groeperings, nl. bogronde, ondergronde met 'n S:K verhouding <0.75 en ondergronde met 'n S:K >0.75, is verder in 7 silk plus klei persentasieklasse per groep ingedeel. Vir die ondergronde met 'n S:K <0.75 was daar net 6 klasse. Die gemiddelde waterretensie- en tekstuurdata per klas is in die regressie-analieses gebruik. Die afgeleide. punt pedo-oordragfunksies tussen waterinhoud en slik plus klei-inhoud, vir elk van die matrikspotensiaalwaardes, was kromJyning. Die akkuraatheid van die waterinhoudwaardes wat met die afgeleide vergelykings voorspel is, is bepaal deur die voorspelde. waardes met die gemete waardes te vergelyk. Die volgende statistiese indikatore, nl. die gemiddelde absolute fout (mMAE), gemiddelde vierkantswortel van die som van kwadrate fout (mRMSE), gemiddelde oorhellingsfout (mMBE), d-indeks van ooreenstremrning en die koëffisiënt van bepaling (R2), is gebruik om die akkuraatheid van die beraamde waterinhoude te bereken. Die slik plus klei funksies van die volledige datastel het 77.6 tot 87.4% van die variasie in waterinhoud by 'n spesifieke matrikspotensiaal verklaar. Die mMBE het tussen -0.001 tot -0.003 crrr' ern", die mMAE 0.022 tot 0.034 cm" cm", die RMSE 0.027 tot 0.042 cm" cm" en die d-waarde tussen 0.84 tot 0.87. gewissel. Vir die bogronde alleen het die slik plus klei-inhoude 88 tot 94.3% van die variasie in waterinhoud verklaar met die mMBE wat tussen 0 en -0.001 cm' cm", mMAE 0.018 en 0.031 cnr' cm", mRMSE 0.024 en 0.036 cm3 cm" en die d-waardes 0.77 en 0.89, gewissel het. Vir die ondergronde met S:K verhoudings <0.75 het die slik plus kleiinhoude 78.3 tot 86.9% van die variasie in waterinhoud verklaar met mMBE-waardes tussen -0.001 en -0.004 cm" cm", mMAE 0.019 en 0.036 cm'' cm", mRMSE 0.023 en 0.045 cm' cm" en d-waardes tussen 0.79 en 0.88. Vir die ondergronde met S:K verhoudings >0.75 was die ooreenstemmende indikatore 85.5 tot 97.6%, mMBE - 0.001 tot 0.004 cm3 cm", mMAE 0.013 tot 0.031 crrr' cm", mRMSE 0.015 tot 0.038 crrr' ern" en d-waardes tussen 0.74 en 0.99. Van die ses waterretensiefunksies wat getoets is, het die Van Genuchten (1980) funksie, met 'n beperking van m = 1 - l/n, die beste passing in alle gevalle gegee, gevolg deur die Smith (1992) en gewone magsfunksies. Oor die algemeen het die Brooks & Corey (1964) funksie die swakste gevaar. Die parameters van die Smith (1992) en Hutson & Cass (1987) funksies het die beste met verskillende grondeienskappe gekorreleer. Met die parametriese benadering het die Smith (1992) vergelyking die waterinhoude van die bogronde en die ondergronde met S:K >0.75, die akkuraatste beraam en vir ondergronde met S:K <0.75 was die Hutson & Cass vergelyking die beste. Die afgeleide punt en parametriese pedo-oordragfunksies is op 'n onafhanklike datastel getoets. Geen verskil kon tussen die akkuraatheid van die voorspelde waardes van die twee benaderings gevind word nie, hoewel die puntbenadering effens beter voorspellings vir bogronde gegee het.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2003
Keywords: Water content; Water retention characteristic curve; Matric potential; Pedotransfer functions; Silt plus clay content; Silt to clay ratio; Water retention functions; Soil moisture -- Ethiopia; Soils -- Ethiopia.